2020
DOI: 10.1155/2020/3176521
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Adiponectin Single Nucleotide Polymorphisms and Side Effects of Isotretinoin in Acne Patients

Abstract: Background. Acne is a common condition of pilosebaceous follicle especially among young. Clinically, the most used medication in the treatment of moderate to severe acne is oral isotretinoin. However, interindividual variability in therapeutic response to isotretinoin and many side effects such as musculoskeletal pain, headache, and alteration in lipid profile can be seen with this treatment. Aim. In this study, the effect of genetic polymorphisms, rs2241766 and rs1501299, of the adiponectin gene was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Isso afeta o metabolismo, a regulação imunológica e a inflamação. Estudos de Garba et al (2020) Em conclusão, a resposta e as alterações lipídicas associadas ao tratamento com isotretinoína oral estão correlacionadas com variações genéticas no rs7799039 do gene LEP. O genótipo CC do rs7799039 do LEP mostrou a maior resposta e o menor aumento nos níveis de AST e CT. Os genótipos CC e AC estão associados a uma diminuição significativa no IGF-1 em pacientes com acne vulgar.…”
Section: Resultsunclassified
“…Isso afeta o metabolismo, a regulação imunológica e a inflamação. Estudos de Garba et al (2020) Em conclusão, a resposta e as alterações lipídicas associadas ao tratamento com isotretinoína oral estão correlacionadas com variações genéticas no rs7799039 do gene LEP. O genótipo CC do rs7799039 do LEP mostrou a maior resposta e o menor aumento nos níveis de AST e CT. Os genótipos CC e AC estão associados a uma diminuição significativa no IGF-1 em pacientes com acne vulgar.…”
Section: Resultsunclassified
“…8 Following isotretinoin treatment, changes in lipid profile (total cholesterol and triglycerides) and liver enzymes (aspartate transaminase and alanine transaminase) have been recorded. 6,9 A recent study done during 2021 in Qassim University Medical City, Saudi Arabia, showed triglyceride levels and total cholesterol were elevated at the end of treatment course, 12.7% and 9%, respectively. Obesity was the major factor associated with high triglyceride levels, with a significant association between body weight and elevation of triglyceride levels.…”
Section: Introductionmentioning
confidence: 99%
“…5 The possible side effects of isotretinoin including joint discomfort, headache, mucosal dryness, and nose bleeds were the most frequent side effects of isotretinoin treatment, along with lipid profile and liver enzyme changes. 6,7 Interestingly, a study conducted in Al-Ahsa, Saudi Arabia, showed that more than half of participants (58.7%) did not consider lipid profile changes as a risk of using isotretinoin. 8 Following isotretinoin treatment, changes in lipid profile (total cholesterol and triglycerides) and liver enzymes (aspartate transaminase and alanine transaminase) have been recorded.…”
Section: Introductionmentioning
confidence: 99%
“…18 This gene is 17 kb long and consists of 3 exons and 2 introns. 19 ADIPOQ SNPs are associated with an increased risk of many diseases including atherosclerosis, 20 rheumatoid arthritis, 21 acne vulgaris 19 and atopic dermatitis, 22 but have not evaluated in AA until now.…”
Section: Introductionmentioning
confidence: 99%